The chaperone [large type] - Moriarty, Laura, 1970- (Thorndike Press large print core series., 2012)
Accompanying a future famous actress from her Wichita home to New York, chaperone Cora Carlisle shares a life-changing five-week period with her ambitious teenage charge during which she discovers the promise of the 20th century and her own purpose in life.